Proceedings of the 2016 Internet Measurement Conference 2016
DOI: 10.1145/2987443.2987469
|View full text |Cite
|
Sign up to set email alerts
|

"Recommended For You"

Abstract: One advertising format that has grown significantly in recent years are known as Content Recommendation Networks (CRNs). CRNs are responsible for the widgets full of links that appear under headlines like "Recommended For You" and "Things You Might Like". Although CRNs have become quite popular with publishers, users complain about the low-quality of content promoted by CRNs, while regulators in the US and Europe have faulted CRNs for failing to label sponsored links as advertisements. In this study, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…They also reported that the whiltelisting process is flawed because "acceptable" ads are often disliked by users due to their intrusiveness and misleading resemblance to page content. In fact, the whitelisting of deceptive ads from content recommendation networks such as Taboola and Outbrain [17] has been quite controversial [3]. Pujol et al [60] showed that most ABP users do not opt-out of the Acceptable Ads whitelist despite these issues.…”
Section: A Whitelistingmentioning
confidence: 99%
“…They also reported that the whiltelisting process is flawed because "acceptable" ads are often disliked by users due to their intrusiveness and misleading resemblance to page content. In fact, the whitelisting of deceptive ads from content recommendation networks such as Taboola and Outbrain [17] has been quite controversial [3]. Pujol et al [60] showed that most ABP users do not opt-out of the Acceptable Ads whitelist despite these issues.…”
Section: A Whitelistingmentioning
confidence: 99%